Impaired ARID1A expression attenuated the immune response in gastric cancer via histone acetylation - Yu Tang; Ruizhi Zhang; Gan Mao; Chong Li; Yisong Gao; Xuebing Zhou; Wenxiang Nie; Tianyu Song; Suao Liu; Kaixiong Tao; Peng Zhang; Wei Li (Clinical Epigenetics)
Abstract Background The primary objective of this study was to examine whether ARID1A mutations confer a fitness advantage to gastric cancer from an immunological perspective, along with elucidating the underlying mechanism. Additionally, we aimed to identify the clinical potential of combining epigenetic inhibitors with immune checkpoint inhibitors to improve the efficacy of immunotherapy for gastric cancer. Methods The correlation between ARID1A gene expression and gastric cancer patient survival was analyzed using the GEO dataset GSE62254. The association between chemokines (CXCL9, CXCL10) and ARID1A was conducted using GSE15460 dataset. Real-time PCR was employed for gene expression analysis, while chromatin immunoprecipitation was used to identify transcriptional regulation on target genes. Protein expression and regulation were assessed through various techniques, including Western blot, ELISA, immunohistochemistry, and immunofluorescence. Chromatin DNA accessibility was determined through MNase digestions, transmission electron microscopy, and ChIP-seq. The impact of ARID1A expression and epigenetic inhibitors on tumor immunity in mice was assessed using flow cytometry. Results ARID1A expression demonstrated a positive correlation with CD8+ T cell infiltration and clinical prognosis. The loss of ARID1A expression led to impaired Th1-type chemokines. Additionally, ARID1A depletion was associated with enhanced tumor growth and the absence of CD8+ T cells within the tumor microenvironment. The study revealed that ARID1A played a role in promoting histone acetylation and facilitating chromatin accessibility. Notably, the application of deacetylase inhibitors effectively reversed the effects of ARID1A depletion on tumor progression and significantly enhanced the efficacy of immunotherapy. Conclusion Gastric cancer with ARID1A mutations modulates immune cell chemotaxis within the tumor microenvironment by influencing histone acetylation. Deacetylase inhibitors have the potential to alter the secretion of chemokines for tumor immune cells, consequently enhancing the effectiveness of immune checkpoint inhibitor therapy in ARID1A-mutated gastric cancer.